PERANCANGAN BOX MAKANAN DAN MINUMAN UNTUK DIGUNAKAN DI MOBIL DENGAN MEMANFAATKAN KOMPONEN MOBIL - Rani Eva Dewi; Kresno Soelasmono; Kumara Sadana Putra (Perpustakaan Universitas Surabaya, 2018)
Abstract - Private vehicles , favorite most of the indonesia to conduct a long trip instead of using public transport .By a vehicle personal , the community needs to bring in food or drink in doing a long trip .In addition , with bring in food and drink own , stamina would remain maintained during a .This research has objective to design box for carrying food and drink while traveling to distance by use components car. The use of components this car to obtain a temperature hot and cold to be used in box .This research in a qualitative by interviewing to users of private vehicles and observation on the stuff relating to design. In addition, done experiment to components the car that will used. The result of peneitian this is box for food and drink that is function temperature hot and cold at once.Box it helps to bring in food and drink during a with private vehicles.